1976
DOI: 10.1007/bf00446561
|View full text |Cite
|
Sign up to set email alerts
|

Ion metabolism in a halophilic blue-green alga, Aphanothece halophytica

Abstract: The intracellular ion content of the halophilic blue-green alga, Aphanthece halophytica was studied as a function of age, external sodium and external potassium concentration. Intracellular Na+ was found to be about 0.38 millimoles/g dry mass. Intracellular K+ concentrations were as high as 1 M and varied directly with external salinity. Intracellular Ca++ and Mg++ were in the range previously reported for fresh water blue-green algae despite their extremely high extracellular concentrations. Average cell size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1981
1981
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…The photoautotrophic nitrogen-fixing cyanobacteria, in general, exhibit considerable tolerance to salt or osmotic stress (30) and reclamation of saline/sodic soils using these organisms has been attempted with some success (25). Adaptation to salt stress in cyanobacteria, although not adequately understood, consists of at least three phenomena: (a) accumulation of internal osmoticum in the form of inorganic ions (17) or organic solutes (6,15,20,22); (b) contribution of ion transport processes (1, 2, 4, 21, 23, 30); and (c) metabolic adjustments (7,30).…”
Section: Organisms and Growth Conditionsmentioning
confidence: 99%
“…The photoautotrophic nitrogen-fixing cyanobacteria, in general, exhibit considerable tolerance to salt or osmotic stress (30) and reclamation of saline/sodic soils using these organisms has been attempted with some success (25). Adaptation to salt stress in cyanobacteria, although not adequately understood, consists of at least three phenomena: (a) accumulation of internal osmoticum in the form of inorganic ions (17) or organic solutes (6,15,20,22); (b) contribution of ion transport processes (1, 2, 4, 21, 23, 30); and (c) metabolic adjustments (7,30).…”
Section: Organisms and Growth Conditionsmentioning
confidence: 99%
“…Aphanothece halophytica is a halophilic cyanobacterium, unable to grow at or below 3.5% (w/v) NaCl (sea water salinity) (5). The osmotic adaptation of this organism was first studied by Miller et al (15) who showed that A. halophytica accumulated up to 1 M K+ in response to increasing external salinity. Recently, Reed et al (18) demonstrated that betaine is the major solute accumulated followed by K+ in four strains of cyanobacteria including A. halophytica grown in high salinity.…”
mentioning
confidence: 99%
“…Intracellular K + in Aphanothece halophytica was shown to be as high as 1 mol . dm-3, varying as a direct function of external salt concentration [47,48]. This suggests that halophilic cyanobacteria and non-halotolerant forms [49] may possess dissimilar K + transport mechanisms although more precise data for K f fluxes etc.…”
Section: Discussionmentioning
confidence: 99%